1998
DOI: 10.1002/(sici)1521-4141(199812)28:12<4123::aid-immu4123>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

γ-glutamyl transpeptidase, an ecto-enzyme regulator of intracellular redox potential, is a component of TM4 signal transduction complexes

Abstract: CD21 (C3dg/EBV receptor) is physically associated on B cells with a complex of proteins that includes CD19 and the widely distributed tetraspan 4 (TM4) family protein CD81 as well as other TM4 proteins (CD53, CD37 and CD82). Monoclonal antibodies (mAb) were generated that blocked homotypic adhesion induced by CD21 ligands in the human B cell line Balm-1. One inhibitory mAb (3A8) was found to recognize the ecto-enzyme gamma-glutamyl transpeptidase (GGT), a membrane protein involved in recycling extracellular gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…CD63 and other tetraspanins can be coimmunoprecipitated with type II phosophoinositide 4-kinase (39,40) and ␥-glutamyl transpeptidase (41). The presence of these enzymes suggests that their recruitment to specific tetraspanin-rich areas of membranes may mediate regulated signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…CD63 and other tetraspanins can be coimmunoprecipitated with type II phosophoinositide 4-kinase (39,40) and ␥-glutamyl transpeptidase (41). The presence of these enzymes suggests that their recruitment to specific tetraspanin-rich areas of membranes may mediate regulated signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the second possibility, that hCR2 alters homotypic adhesion, previous studies have shown that engagement of CR2 promotes homotypic adhesion of B cell lines (29,52), most likely in a CD19/CD81-dependent manner. Based on these findings, and the postulated importance of B cell:B cell homotypic interactions during bone marrow development (2), it is possible that the binding of ligand to hCR2 could alter this process in a detrimental manner.…”
Section: Discussionmentioning
confidence: 99%
“…GGT expression on primary B cells and Ramos transfectants was determined by flow cytometry using the monoclonal antibody, 3A8 (15). GGT enzymatic activity in whole cell lysates was determined using a commercially available kinetic assay for the conversion of L-␥-glutamyl-3-carboxy-4-nitroanilide to 5-amino-2-nitrobenzoate in the presence of glycylglycine (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Cells-Using a recently developed monoclonal antibody (3A8) to human GGT (15) and flow cytometry, expression of GGT by human T lymphocytes was previously found to increase with cellular activation (6). The same approach was used to assess the level of GGT expression on human B lymphocytes.…”
Section: Ggt-transfected Ramos Cells As a Model Of Activated Bmentioning
confidence: 99%